Deep Learning Algorithm for Automated Detection of Polycystic Ovary Syndrome Using Scleral Images - Lv, Wenqi; Song, Ying; Fu, Rongxin; Lin, Xue; Su, Ya; Jin, Xiangyu; Yang, Han; Shan, Xiaohui; Du, Wenli; Huang, Qin; Zhong, Hao; Jiang, Kai; et al. (Frontiers in Endocrinology, 2022)
The high prevalence of polycystic ovary syndrome (PCOS) among reproductive-aged women has attracted more and more attention. As a common disorder that is likely to threaten women’s health physically and mentally, the detection of PCOS is a growing public health concern worldwide. In this paper, we proposed an automated deep learning algorithm for the auxiliary detection of PCOS, which explores the potential of scleral changes in PCOS detection. The algorithm was applied to the dataset that contains the full-eye images of 721 Chinese women, among which 388 are PCOS patients. Inputs of the proposed algorithm are scleral images segmented from full-eye images using an improved U-Net, and then a Resnet model was applied to extract deep features from scleral images. Finally, a multi-instance model was developed to achieve classification. Various performance indices such as AUC, classification accuracy, precision, recall, precision, and F1-score were adopted to assess the performance of our algorithm. Results show that our method achieves an average AUC of 0.979 and a classification accuracy of 0.929, which indicates the great potential of deep learning in the detection of PCOS.